P503 An eye-opening case aniscoria. (June 2019) - Jenkins, Elinor; Webb, David W; Regan, Mary O
Abstract : Introduction: Aniscoria is a condition characterised by pupils of unequal size. Aniscoria may be completely benign and physiological. However it can also be associated with serious life-threatening conditions and therefore prompts alarm in clinicians. Case Description: A 4-year-old boy referred by his family doctor to hospital with a sudden onset dilated and un-reactive left pupil. His mother had noticed the abnormal pupil on waking that morning, approximately 6 hours earlier. Her son did not appear to be in pain and his vision was unaffected. He appeared to be rubbing his eye at times but his awareness and behaviour were unaltered. There was no history of trauma and he was systemically well. Background: This little boy had a known diagnosis of Creatine Transporter Deficiency, an inherited metabolic disorder associated with learning disability and epilepsy. Physically he was mobile and very active with a mild torticollis, recurrent epistaxis and a tendency to salivate excessively. There was no recent history of headache, nausea or change in seizures. Medications at the time of presentation included Epilim Chrono (450 mg nocte), Flixotide (125 mcg) and a Scopoderm patch. Examination confirmed a fixed dilated left pupil with a left esotropia but otherwise normal eye movement, no ptosis and no obvious conjunctival injection. His neurological exam revealed no altered awareness and no motor deficit. Discussion: Aniscoria is common - found in approximately 20% of children (Fierz, F et al 2017). However the asymmetry is mild and pupil reactive. Aniscoria of > 1.3 mm is unlikely to be physiologic in children and warrants careful assessment (Suh et al 2016). In the absence of a third nerve lesion or trauma to the eye, application of a pharmacological agent with mydriatic effect is the most likely explanation in childhood. Scopoderm patches have been reported as causing aniscoria in a 30-year-old nurse (Shah et al, 2017) and a 14-year-old boy (Lin, 2001). A recent article explored the use of hyoscine patches to reduce drooling in children with neurodisability (Parr et al, 2017) citing aniscoria as one of a number of side-effects when compared to glycopyrronium liquid. Conclusion: Following discussion with his mother involvement of his scopoderm patch was considered to be the most likely cause of his dilated pupil and no further investigations were felt necessary. His mydriasis fully resolved over three days. Children with a neuro-disability can be extremely active -making it hard to keep medication out of their way!